Caracterização físico-quimica e nutricional e avaliação do potencial prebiótico e antioxidante do liofilizado de cladódios de palma [Opuntia dillenii (Ker Gawl). Haw.] - Rocha, Sara de Sousa (2024)
The palm [Opuntia dillenii (Ker Gawl). Haw.] is a cactus considered as a non-conventional food plant (NCFP) belonging to the Caatinga biome and found mainly in the semiarid regions of the Brazilian Northeast. O. dillenii stands out for containing several bioactive compounds with anti-inflammatory and antioxidant properties, so its cladodes are evaluated as aids in the treatment of diseases such as gastritis, diabetes and dyslipidemia, although studies seeking to elucidate its composition are still scarce. nutritional and functional potential as a vegetable for human consumption. This study aimed to investigate physicochemical parameters and the antioxidant and prebiotic potential of O. dillenii cladode freeze-dried (LCP) in an in vitro fermentation system. To this end, after preparing the freeze-dried product, analyzes were carried out to determine physical-chemical parameters and indicators of prebiotic activity and antioxidant capacity in an in vitro fermentation system using human fecal inoculum. According to the results obtained, the LCP presented high levels of total fiber (52.63 g/100 g), soluble fibers (33.36 g/100g) and insoluble fibers (19.00 g/100 g), proteins (16.84 g/100 g) and lipids (4.98 g/100 g). High amounts of total chlorophyll (912.00 mg/100 g), chlorophyll a (565.00 mg/100 g) and chlorophyll b (349.00 mg/100 g) were observed, in addition to the presence of nine minerals, notably for macroelements such as potassium (4415.49 mg/100 g), calcium (1593.25 mg/100 g), sodium (1010.52 mg/100 g) and magnesium (853.55 ± 10.69 mg/100 g) , and microelements such as manganese (8.92 mg/100 g), zinc (5.95 mg/100 g) and iron (3.72 mg/100 g). Sixteen phenolic compounds were identified, with the highest prevalence being myricetin (785 mg/100 g), caftaric acid (265 mg/100 g) and hesperidin (135 mg/100 g). Among the organic acids detected in the LCP, the highest quantities were malic (16.84 g/L), citric (4.43 g/L) and succinic (3.26 g/L). Fecal fermentation of LCP for 48 h promoted a reduction (p ≤ 0.05) in the values of phenolic compounds, such as catechin, myricetin, isorhamnetin and rutin, as well as organic acids, such as malic, formic and acetic acids, indicating the occurrence of biochemical transformations and the metabolization of these compounds by microorganisms that form the fecal microbiota. There was an increase in antioxidant activity in the fermentation medium containing LCP when evaluated by the ABTS•+ and FRAP methods, and a reduction (p ≤ 0.05) when evaluated by the DPPH• method. After 48 h of fecal fermentation, the medium containing LCP showed greater bacterial diversity and a higher Firmicutes:Bacteroidetes (F:B) ratio when compared to the positive control (medium containing fructooligosaccharides). Furthermore, changes were observed in the composition of the intestinal microbiota in the medium containing LCP, with emphasis on the increase in the relative abundance of Ligilactobacillus and Lactiplantibacillus, to the detriment of the decrease in Prevotella_9 and Succinivibrio. Several metabolites were detected using the nuclear magnetic resonance technique in the medium containing LCP, including acetate, propionate and butyrate, in addition to amino acids, such as leucine, valine and isoleucine. The results indicate that LCP has a high content of dietary fiber, chlorophyll, minerals, organic acids and phenolic compounds, in addition to antioxidant capacity, thus being able to exert beneficial effects on the composition and metabolic activity of the human intestinal microbiota through prebiotic properties, characterizing It is a potential ingredient for the formulation of functional foods and nutraceuticals.